2021
DOI: 10.1186/s13643-021-01739-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abortion law reforms on women’s health services and outcomes: a systematic review protocol

Abstract: Background A country’s abortion law is a key component in determining the enabling environment for safe abortion. While restrictive abortion laws still prevail in most low- and middle-income countries (LMICs), many countries have reformed their abortion laws, with the majority of them moving away from an absolute ban. However, the implications of these reforms on women’s access to and use of health services, as well as their health outcomes, is uncertain. First, there are methodological challen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…13 In the event of an emergency in a remote location, such as on a ship, in an airplane, or potentially on the battlefield, telemedicine is vital. 14 Research has found that the success rate and safety outcomes of medical abortion through telemedicine appear to be very similar to those reported in the literature for in-person abortion services. 15 In a study of 1000 women who underwent self-sourced medical abortion through an online telemedicine service (Women on Web), its reach to result that self-sourcing medical abortion through online telemedicine can be very successful, and the results are comparable to those of in-clinic methods.…”
Section: Chapter 4 -Telemedicine Abortionsupporting
confidence: 63%
“…13 In the event of an emergency in a remote location, such as on a ship, in an airplane, or potentially on the battlefield, telemedicine is vital. 14 Research has found that the success rate and safety outcomes of medical abortion through telemedicine appear to be very similar to those reported in the literature for in-person abortion services. 15 In a study of 1000 women who underwent self-sourced medical abortion through an online telemedicine service (Women on Web), its reach to result that self-sourcing medical abortion through online telemedicine can be very successful, and the results are comparable to those of in-clinic methods.…”
Section: Chapter 4 -Telemedicine Abortionsupporting
confidence: 63%
“…Abortion emerges as a prominent concern in the realm of global health, with varying incidence rates and backgrounds worldwide 1 . It is of utmost importance to address the consequences of abortion, as it significantly increases morbidity and mortality in pregnant and postpartum women 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Since Dobbs, there have been varying nationwide implementation of bans or protection of abortion access (11) with several states imposing partial or complete abortion restrictions. In conjunction with a woman's location of residency, restrictive abortion laws serve as socio-ecological determinants of abortion care access which can potentially impact her sexual and reproductive health and wellbeing (12)(13)(14). The reversal of Roe vs. Wade has generated substantial concerns among the public.…”
Section: Introductionmentioning
confidence: 99%